The wedding banquet [videorecording (Blu-Ray)] - Ahn, Andrew; Schamus, James, 1959-; Yang, Bowen, 1990-; Gladstone, Lily; Tran, Kelly Marie; Han, Ki-ch'an, 1998-; Le, Bobo; Atebe, Camille; Chen, Joan, 1961-; Yun, Yŏ-jŏng, 1947-; Kim, Ki Jin; Wadley, Jay (Decal, 2025)
Angela and her partner Lee have been unlucky with their IVF treatments but can't afford to pay for another round. Meanwhile their friend Min, the closeted scion of a multinational corporate empire, has plenty of family money but a soon-to-expire student visa. When his commitment-phobic boyfriend Chris rejects his proposal, Min makes the offer to Angela instead: a green card marriage in exchange for funding Lee's IVF. But their plans to quietly elope are upended when Min's skeptical grandmother flies in from Korea unannounced, insisting on an all-out wedding extravaganza.